Pricing response to entry and agglomeration effects - McCann, Brian T.; Vroom, Govert (Strategic Management Journal, 2010)
In contrast to the traditional approach that typically views entry solely as a threat, we argue that our understanding of this important phenomenon will remain incomplete until we consider the possibility that entry may also provide opportunity for incumbent firms. Drawing from agglomeration theory, which describes the benefit from colocating with competitors, we explicitly examine the combined impact of the competitive and agglomeration effects of entry using a unique dataset of Texas hotels. We find that incumbent establishments price higher when facing entrants whose agglomeration benefits are more likely to outweigh their competitive effects. This association is stronger for incumbents that have greater experience with entry. Our results bring a new perspective to the entry response literature helping clarify inconsistent empirical results. Further, we apply agglomeration theory to a new question, incumbent behavior, and demonstrate that experience appears to play an important role in recognizing situations that generate agglomeration externalities. Copyright © 2009 John Wiley & Sons, Ltd.